Fiqhi Exegesis: History, Methodology and Its Relevance within the ‎Framework of Maqasid al-Shariʿah - Ihdal Umami Jahira; Abd. Kholid (Jurnal Ulunnuha, 2025)
This study offers a comprehensive analysis of tafsir fiqhi within the framework of madzhāhib al-tafsīr and examines its relevance in contemporary maqāṣid al-sharī‘ah discourse. The background of this research lies in the growing need for Islamic legal interpretation that is not only textually grounded but also capable of responding to emerging socio-legal challenges such as digital transactions, bioethics, environmental issues, and human rights. Unlike previous studies that merely describe legal exegesis as a branch of Qur’anic interpretation, this research re-positions tafsir fiqhi as a distinct exegetical tradition whose methodology is rooted in uṣūl al-fiqh, qirā’āt analysis, and muqāranat al-madhāhib. This study employs a qualitative library-based approach with descriptive-analytical methods, drawing on classical and contemporary tafsir works as well as academic studies on Islamic legal interpretation. The findings indicate that tafsir fiqhi has historically served as a crucial bridge between revelation and legal practice, while in the modern context its ethical orientation can be strengthened through the integration of maqāṣid al-sharī‘ah. Such integration allows tafsir fiqhi to remain faithful to its classical methodological foundations while ensuring that legal interpretation remains responsive to public welfare and contemporary realities. The study concludes that tafsir fiqhi, when viewed through the lens of madzhāhib al-tafsīr and re-oriented toward maqāṣid al-sharī‘ah retains strong relevance as a normative-contextual framework for modern Islamic legal thought.